Analysis of Nasal Septal Deviation Types on Sinusitis Incidence: Literature Review - Ristyana, Sabira Husna; Povitasari, Povitasari; Andarista, Aprilia Intan; Adji, Iwan Setiawan (Journal La Medihealtico, 2025)
Nasal septal deviation is a common anatomical abnormality found in the general population and is thought to play a role in the pathogenesis of sinusitis. Some types of nasal septal deviation can impair sinus drainage and airflow, leading to inflammation and infection. However, there is no consensus on which type of septal deviation contributes most to sinusitis. Objective: This literature review aims to analyze and identify the types of nasal septal deviation that are most frequently associated with sinusitis. Methods: The data review was conducted using the PRISMA method, with data searches from PubMed, Google Scholar, ScienceDirect and Wiley with research data criteria between 2020-2024. The keywords used to search for data were "Type", "Nasal Septal Deviation", and "Sinusitis". A total of 23,943 articles were screened, with the final result being 20 articles that met the criteria for review. Results: Based on the review of the review in this study, nasal septal deviation (SND), especially types 3 and 5 according to the Mladina classification, contributes to chronic sinusitis through impaired ventilation and sinus drainage. Discussion : Nasal septal deviation (SND) is an anatomical abnormality that can interfere with airflow and sinus drainage, thus playing a role in the pathogenesis of sinusitis, especially types 3 and 5 according to the Mladina classification. These two types are often associated with osteomeatal complex obstruction and chronic mucosal irritation. The mechanisms involved include local hypoxia, mucociliary disorders, chronic inflammation, and changes in the microbiome.